ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MASYARAKAT BEROBAT DI PUSKESMAS KECAMATAN BUAYAN - andi hermawan; cokro aminoto; cahyu septiwi (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2011)
A lot of the factors that decide the grade of medical community, it seems the access to health services is hold an important action. Indonesian health development is aiming to reach the realization, willingness, and ability to living well for every people. This research is to find out of factors that related to patients who come to Buayan community health center for having medications. The method in this research is used descriptive cross sectional approximation, with 94 responder’s. Independent variable : medical service, cost, recovery experience, motivation, and distance. Dependent variable: patients who come to Buayan community health center for having medications. To analyze the data used Kendall’s Tau. The research result show, there are relation between health service factor (p = 0,030), cost service factor (p = 0,002), recovery experience factor (p = 0,027), motivation factor (p =0,000), distance factor(p = 0,022) with Patients Who Come to Buayan Community Health Center for Having Medications. . Keywords: Factors, Having